2020
DOI: 10.1007/s10653-019-00499-w
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiencies in African soils and the human nutritional nexus: opportunities with staple crops

Abstract: A synthesis of available agronomic datasets and peer-reviewed scientific literature was conducted to: (1) assess the status of micronutrients in sub-Saharan Africa (SSA) arable soils, (2) improve the understanding of the relations between soil quality/management and crop nutritional quality and (3) evaluate the potential profitability of application of secondary and micronutrients to key food crops in SSA, namely maize (Zea mays L.), beans (Phaseolus spp. and Vicia faba L.), wheat (Triticum aestivum L.) and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 75 publications
2
92
0
Order By: Relevance
“…Soil characteristics and production systems affect crop macro- and micronutritional qualities for human consumption ( Herencia et al, 2011 , Kihara et al, 2020 , Lovegrove et al, 2020 , Shewry, 2018 , Shewry and Hey, 2015a ). More local knowledge is needed.…”
Section: The Dietary Contributions Of Cereal Foodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil characteristics and production systems affect crop macro- and micronutritional qualities for human consumption ( Herencia et al, 2011 , Kihara et al, 2020 , Lovegrove et al, 2020 , Shewry, 2018 , Shewry and Hey, 2015a ). More local knowledge is needed.…”
Section: The Dietary Contributions Of Cereal Foodsmentioning
confidence: 99%
“…Agri-food systems thinking provides a robust platform for reshaping the agri-nutrition research agenda and to incorporate multi-disciplinary partnerships. There are ongoing wheat and maize systems research needs, which are to: accelerate plant breeding for nutritional quality and biofortified crop varieties, and scale up industrial fortification, both being proven strategies for enhancing the nutrient-intensity of major cereals among other crops ( HarvestPlus 2020 ); persist in crop productivity and sustainability research in diverse soil and production conditions and in the context of climate change, especially under the resource-constrained conditions of smallholder farmers ( Ritzema et al, 2017 , Kihara et al, 2020 ); enhance practices for processing, manufacturing, storage and distribution of natural, bio- and industrially enriched cereal foods to reduce losses and nutritional harm in terms of both quality and quantity ( Sharma et al, 2020b ); understand consumer behaviour at a disaggregated level: livelihood patterns and access to different foods among vulnerable groups, in different cultures, and in different production and marketing systems ( Haddad 2020 ); identify the inherent contradictions and resolve the trade-offs within cereal food systems concerning environmental sustainability, poverty reduction, profitability for actors and firms throughout the value chain, and improved nutrition and health of vulnerable populations. …”
Section: Policy Implications: Revisiting the Agriculture Food And Numentioning
confidence: 99%
See 1 more Smart Citation
“…In India, one-third of the cultivated area has calcareous soils that are deficient in iron, mostly distributed in the low rainfall areas, where groundnut is a major crop and suffers from iron deficiency (ID) or interveinal chlorosis leading to a significant decrease in pod yield (16–32%) [ 8 ]. In Sub-Saharan Africa (SSA) arable lands (over 50% of the world’s potential land for cultivation), iron is among the five predominant soil micronutrients being identified as important for crop productivity [ 9 ]. Acute iron deficiency can lead to plant death and even complete crop failure.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria and Togo, Kihara et al. (2020) observed that application of Zn and other macronutrients caused an increase of about 20% in maize grain Zn concentration over a control treatment. In Pakistan, with seed priming, Harris et al.…”
Section: Introductionmentioning
confidence: 99%